Boosting Glioblastoma Therapy with Targeted Pyroptosis Induction - Fang Xinggang; Chen Zhuo; Zhou Wenhui; Li Tongfei; Wang Man; Gao Yujiu; Ma Shinan; Feng Ying; Du Shiming; Lan Peimin; Chen Hanyu; Wei Jiarui; et al. (WILEY-V C H VERLAG GMBH, 2025)
Glioblastoma (GBM) is a highly aggressive cancer that currently lacks effective treatments. Pyroptosis has emerged as a promising therapeutic approach for cancer, but there is still a need for new pyroptosis boosters to target cancer cells. In this study, it is reported that Aloe-emodin (AE), a natural compound derived from plants, can inhibit GBM cells by inducing pyroptosis, making it a potential booster for pyroptosis-mediated GBM therapy. However, administering AE is challenging due to the blood-brain barrier (BBB) and its non-selectivity. To overcome this obstacle, AE@ZIF-8 NPs are developed, a biomineralized nanocarrier that releases AE in response to the tumor's acidic microenvironment (TAM). Further modification of the nanocarrier with transferrin (Tf) and polyethylene glycol-poly (lactic-co-glycolic acid) (PEG-PLGA) improves its penetration through the BBB and tumor targeting, respectively. The results show that AE-NPs (Tf-PEG-PLGA modified AE@ZIF-8 NPs) significantly increase the intracranial distribution and tumor tissue accumulation, enhancing GBM pyroptosis. Additionally, AE-NPs activate antitumor immunity and reduce AE-related toxicity. Overall, this study provides a new approach for GBM therapy and offers a nanocarrier that is capable of penetrating the BBB, targeting tumors, and attenuating toxicity.